-23+x+28=

Simple and best practice solution for -23+x+28= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23+x+28= equation:


Simplifying
-23 + x + 28 = 0

Reorder the terms:
-23 + 28 + x = 0

Combine like terms: -23 + 28 = 5
5 + x = 0

Solving
5 + x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + x = 0 + -5

Combine like terms: 5 + -5 = 0
0 + x = 0 + -5
x = 0 + -5

Combine like terms: 0 + -5 = -5
x = -5

Simplifying
x = -5

See similar equations:

| -2x-8=8x+1 | | 3x(2xy^2+4y^3)=V | | (4x+3)(3x-5)=(4x-3)(3x+5) | | 12x+50=7x-40 | | 5x-5=5(x+7) | | 6+13=6+(n+5) | | .12222= | | 5c+c=78 | | -5x+13=14 | | -2=20x | | 6n^2-18n-168=0 | | 12m-15=-3 | | 3x-0.4=1.4 | | Y+28=x+5 | | 8(x+3)-3x=2(x+12)+3x | | B+ax=2x | | -7v-19=6(1+3v) | | -5(x+3)+8=-7 | | 36w=648 | | 0.4(-5)+6.1= | | 6u^2+u-6=0 | | -2(t-2)+7t=9T-3 | | 3x+7+6x=106 | | -3(y-2)=-2y-1 | | ln(x+1)+ln(3)=ln(2x) | | x-15=4y | | 5.25n=46.50 | | 5*(12-3)=5*e | | 15n=5.25 | | 6a+3+2a=19 | | 8y-16=8y+-16 | | 8=2(4j+1)-5j |

Equations solver categories